Anglo-American Playing Cards Identification Based on Counting Each Symbols and Scale Invariant Feature Transform (SIFT) - E, Nancy Velasco; Mendoza Chipantasi, Dario Jose; Andaluz, Victor H.; Dominguez, Sergio (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper is inspired by detection and identification of Anglo-American playing cards from an image using an entry-level webcam and computer vision. Some authors have been made algorithms for playing card recognition, but the solution of playing card detection and recognition is still in progress. Although one could think of methods, which classify using the upper left and lower right corners of the card where the numbers are, this paper focuses on the novel method. Without reading the card code, we counted each individual symbols in the playing card. We implemented this algorithm in Matlab solving two parts: Locating the card on the image obtained in a controlled environment, and recognizing the cards. The recognition of playing cards was achieved through thresholding combined with color segmentation and the counting of the symbols in playing cards from one to ten and using SIFT for another playing cards.